Nd60Fe30Al10 Glass Forming Magnetic Alloys: a Mechanical Spectroscopy Study at the 300- 560 K Temperature Range - Salva, Horacio Ramon (2012)
The ferromagnetic amorphous phase in rapidly solidified Nd60Fe30Al10 glass forming alloys is investigated in melt spun ribbons (100 µm thick) and in chill cast cylinders (2 mm diameter). The amorphous resulting for these two different quenching rates were characterized by their room temperature hysteresis loops, magnetization and differential calorimetric measurements in the temperature range 300K-900K. The mechanical damping was explored in the 300-560 K temperature range, by measuring the internal friction and the shear modulus in a forced inverted pendulum operating in the frequency range 0.1-10Hz. Simultaneously, the electrical resistance of the samples was measured. The internal friction spectra of both, ribbons and a cylinder, exhibit a local maximum at about 500K, arising in a relaxation mechanism. After some thermal cycles the peak parameters stabilize reaching an apparent activation enthalpy of 1.5 eV and a limit relaxation time τ0 ≈ 0.4-2.5 . 10-17s. In both samples, the electrical resistance largely decreases during the first heating run to 560K and remains unchanged during subsequent thermal cycles. No changes in the elastic modulus or in the damping properties are detected at the Curie temperature of the alloys.